2013
DOI: 10.1177/1532673x13482966
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Reputations and Issue Agendas

Abstract: How do campaigns decide what issues to emphasize for voters? According to most studies, campaigns rely on factors outside of their control-issue salience, party issue ownership, and district ideology. In this article, I argue that campaign messages are designed primarily based on the candidate. I examine the issue content of campaign advertisements from U.S. House and Senate campaigns from 2000 to 2004 and develop a measure that determines if candidates have developed a reputation on a particular issue.When ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…A common strategy for candidates is to capture or own issues important to voters. Since voters are unlikely to change their policy positions during a campaign, candidates are advised to frame their campaigns around issues on which they are seen as competent (Arbour, 2013;Petrocik, 1996;Riker, 1983). For example, if voters care about agriculture and a candidate is a farmer, then that candidate could appeal to voters and be the "agriculture candidate."…”
Section: Literature Reviewmentioning
confidence: 99%
“…A common strategy for candidates is to capture or own issues important to voters. Since voters are unlikely to change their policy positions during a campaign, candidates are advised to frame their campaigns around issues on which they are seen as competent (Arbour, 2013;Petrocik, 1996;Riker, 1983). For example, if voters care about agriculture and a candidate is a farmer, then that candidate could appeal to voters and be the "agriculture candidate."…”
Section: Literature Reviewmentioning
confidence: 99%
“…One line of research follows the theoretical prediction of the Downsian median voter theorem that campaigns will converge to create a dialogue on the same issues (Kaplan, Park, and Ridout ; Sigelman and Buell ; Simon ; Spiliotes and Vavreck ). Other works have found that the issue agendas of campaigns are influenced by local issue priorities (Sulkin and Evans ), the national issue agenda (Ansolabehere and Iyengar ; Brasher ), and a candidate's personal reputation (Arbour ). There has been substantial focus on whether campaigns follow the prediction of issue ownership theory (Petrocik ) that campaigns are more likely to highlight the issues owned by their party…”
Section: Issue Agendas and Biographymentioning
confidence: 99%
“…An extensive literature has developed to demonstrate the importance of candidate biography in campaign rhetoric (Arbour ; Sellers ; Shyles ). Campaigns discuss their candidate's past (broadly defined to include not just biography, but also private sector experience or their record in elected office) in the vast majority of advertisements.…”
Section: Issue Agendas and Biographymentioning
confidence: 99%
See 2 more Smart Citations